2008
DOI: 10.1364/oe.16.021746
|View full text |Cite
|
Sign up to set email alerts
|

Optical MEMS pressure sensor based on a mesa-diaphragm structure

Abstract: An optical MEMS pressure sensor based on a mesa-diaphragm is presented. The operating principle of the sensor is expatiated by Fabry-Perot (F-P) interference. Both the mechanical model and the signal averaging effect of the mesa diaphragm is validated by simulation, which declares that the mesa diaphragm is superior to the planar one on the parallelism and can reduce the signal averaging effect. Experimental results demonstrate that the mesa structure sensor has a reasonable linearity and sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The material of the annular CD was 316L stainless steel with a radius of 4600 µm, a thickness of 30 µm, a corrugation depth of 60 µm and a corrugation width of 750 µm. Experimental results showed that the sensor had good linearity over the pressure range of 0~0.1 MPa, and the sensitivity was up to 518 µm /MPa, compared with the pressure sensor with the boss structure in the central area of the diaphragm which, was designed by their group [57] in 2008; the sensitivity was increased by two orders of magnitude. In 2017, Zhu Jiali et al [20] designed and fabricated an annular CD-based fiber-optic pressure sensor with a novel F-P structure, which further improved the sensitivity of the sensor and reduced the influence of temperature on the measurement accuracy of the sensor.…”
Section: In the Miniature Fiber-optic Static Pressure Sensorsmentioning
confidence: 97%
“…The material of the annular CD was 316L stainless steel with a radius of 4600 µm, a thickness of 30 µm, a corrugation depth of 60 µm and a corrugation width of 750 µm. Experimental results showed that the sensor had good linearity over the pressure range of 0~0.1 MPa, and the sensitivity was up to 518 µm /MPa, compared with the pressure sensor with the boss structure in the central area of the diaphragm which, was designed by their group [57] in 2008; the sensitivity was increased by two orders of magnitude. In 2017, Zhu Jiali et al [20] designed and fabricated an annular CD-based fiber-optic pressure sensor with a novel F-P structure, which further improved the sensitivity of the sensor and reduced the influence of temperature on the measurement accuracy of the sensor.…”
Section: In the Miniature Fiber-optic Static Pressure Sensorsmentioning
confidence: 97%
“…However, the underlying microsilicon technology is of major significance because it helped fuel revolutionary growth in non-resonant fibre-optically addressed MEMS [8] and silicon-on-insulator (hybrid silicon) photonics [9][10][11][12]. Often exploiting interferometric methods of signal transduction, such technologies are used in both sensing and interrogation.…”
Section: Fibre-optic Microelectromechanical Systems (Mems)mentioning
confidence: 99%
“…Optical fiber sensors based on F-P interferometer are widely used in acoustic and pressure detection due to their high sensitivity and wide frequency spectrum response, which are determined by the acoustic diaphragm fabricated with the MEMS technology [4]. Researchers employed many different techniques to sense a wide variety of measurands which include pressure [5][6][7], sound [4], strain [8][9][10], temperature [10], and displacement [11], while employed different diaphragm structures which include flat diaphragm [4][5][6][7][8][9][10][11], corrugated diaphragm [12], mesa-diaphragm [6], and photoniccrystal diaphragm [13][14][15]. The diaphragm of the F-P sensor sensing acoustic signals is a separate extrinsic sensing element.…”
Section: Introductionmentioning
confidence: 99%